Characterization In-Situ of Diode Detectors for Six-Port receivers - Barbon, Francesco; Lindner, Stefan; Mann, Sebastian; Linz, Sarah; Weigel, Robert; Kölpin, Alexander (Testmethoden und Zuverlässigkeit von Schaltungen und Systemen (TuZ), 2013)
Six-Port receivers require a precise power mea- surement thus a characterization in-situ of its power detector is necessary. The industrial working ambient requires a constant performance monitoring due to temperature drift, fabrication and component tolerances. The detectors’ performance may have some degradation, which limits the measurement accuracy. Thus, an in-situ detector characterization is necessary. In this paper, a fast and simple solution for estimating the diode detectors’ char- acteristics is presented, which is ideal for Six-Port diode power detectors. This method is fast and can be easily implemented on a microcontroller.
elib2cris::1512001600,barbon2013
Keywords: six-port; diode detector; power measurement; in-situ